European Investment Bank Group Fraud Investigations Activity Report 2019 - European Investment Bank (2020)
This Fraud Investigations Activity Report covers the activities of the Inspectorate General's Fraud Investigations Division (IG/IN) in 2019. It provides an overview of the work undertaken by IG/IN to prevent, detect, investigate and remedy Prohibited Conduct affecting EIB Group activities.The report provides in particular:Relevant statistics and their analysis on the number of allegations received and investigations conducted;A variety of internal and external case studies highlighting the different types of allegations handled by the EIB Group investigators as well as the findings and lessons learned;An overview of 10 years of Proactive Integrity Reviews at EIB and of the fraud detection tool developed by IG/IN;Information on the policy work done by IG/IN, such as fraud and corruption awareness initiatives for EIB Group staff members, and its increased efforts in outreach and global partnerships.